Employability skills for future marketing professionals. Issue 3 (June 2019) - Di Gregorio, Angelo; Maggioni, Isabella; Mauri, Chiara; Mazzucchelli, Alice
Abstract: This study investigates how digital transformation has disrupted the marketing career path by analysing the most in-demand marketing skills and identifying opportunities for future marketing professionals. Through a content analysis of job advertisements and a cross-country survey of marketing professionals, the study proposes a framework defining the skillset required of marketing professionals to start and move forward in their career. The study identifies five employability skill categories and 29 skills and capabilities. The relevance of such categories is also analysed across lowly and highly digitalised firms. This research contributes to the debate on the employability of new graduates and provides useful directions to universities, tertiary education institutions, and companies to support the marketing talents of the future.